Educational Campaign on the Advantages of Using Splints as a Non-Pharmacological Approach to Alleviate Pain in Patients After Fractures at Grandmed Lubuk Pakam Hospital (JURNAL PENGMAS KESTRA (JPK), 2025)
This Community Service Program (PKM) aims to provide education on the use of splints as a non-pharmacological therapy for reducing pain post-fracture. The activity was conducted at Grandmed Lubuk Pakam Hospital, involving 25 participants, who were the immediate family members of patients with closed fractures. The education was carried out using a participatory educational approach, employing pre-post tests to measure the improvement in participants' knowledge before and after the intervention. The analysis results showed a significant increase in knowledge, with the average pre-test score of participants being 56.05, which increased to 89.98 in the post-test, with an average knowledge increase of 33.93 points. This improvement was observed across all categories of material presented, such as the benefits of splints, proper splinting techniques, and non-pharmacological pain management. This indicates that the education successfully enhanced the participants' understanding of the benefits of using splints to reduce pain post-fracture. The program also successfully increased the active participation of participants in the practice of splinting, demonstrating that direct demonstration education methods are highly effective. This program shows that the use of splints can be a safe alternative to reduce dependency on painkillers. Furthermore, the education provided a deeper understanding of non-pharmacological therapy that can accelerate the recovery process for fracture patients. Overall, the results of this PKM provide a more effective and safer solution for managing pain in fracture patients, minimizing the use of potentially risky medications.